Evaluation Of The Position Of Lower İncisors By Different Cephalometric Analysis - Seda Haydar; Bülent Haydar (Galenos Yayinevi, 1999)
Three different analyses were evaluated to determine the positions of the lower incisors on lateral head films in high angle and normal morphology patients. A total of 52 subjects were evaluated . Results indicated variability in the positions of the lower incisors depending on the measurement method used and the morphology of the patients.Incisor positions were determined as retroclined (score 0), upright (score 1) or proclined (score 2) for the three analyses also regarding their standard deviations. In the normal morphology group significant differences were noted among Lowerl-NB°and IMPA° (p< 0,001), and IMPA° and Bl/A-P ogonion° (p< 0,001) values.IMPA values tended to show the cases rather more proclined than the other two measurements. In the high angle cases statistically significant difference between IMPA° and Bl/A-P ogonion° (p< 0,05) values were obtained regarding the position of lower incisor. It is clear that a particular analysis to be of choice will show variable lower incisor positions and may affect the treatment approach used.